Consecuencias del cumplimiento parcial de los acuerdos de la consulta previa en el lote 192 (ex 1ab) de la Región Loreto, 2015-2021 - Murayari Perez, Estefany (2024)
Prior Consultation is a fundamental and exclusive right enjoyed by indigenous peoples when it is intended to adopt administrative or legislative measures that directly affect their collective rights. It is necessary to mention that the agreements that were established in a Prior Consultation are decisions adopted and mandatory by the State and the indigenous peoples; Therefore, the objective of this investigation is to determine the consequences that arise from partial compliance with the agreements established in the Prior Consultation in Lot 192 (ex 1AB) signed in 2015, based on the roles of the State, the indigenous people and private companies. The following methodology is used: Qualitative research, and within the field of pure scientific research, it is a basic type of research, at an exploratory level, and within the field of legal research it has components of both dogmatic and of a sociological-functional investigation. The conclusion is that partial compliance with the agreements signed in the minutes of Prior Consultation causes social conflicts: On the part of the State, it generates abandonment of the indigenous peoples, because it is not fulfilling its function of safeguarding their interests and rights; In indigenous peoples, it generates tireless protests in the oil fields in such a way that in some cases they block entry to the concession area, roads and rivers; On the other hand, private companies are the most benefited, since they continue to carry out their work of extracting hydrocarbons, and in the face of protests they only tend to file complaints for damages, disturbances or attacks against common security. Consequently, the violation of primary rights such as the right to life, integrity, property, work, free movement and personal freedom is noted. Likewise, it is pertinent to mention that compliance with the agreements reached in a Prior Consultation is enforceable both at the administrative and judicial level, and in the latter it is through the amparo action.